A Decomposable Branching Process in a Markovian Environment. (31st December 2012) - Vatutin, Vladimir; Dyakonova, Elena; Jagers, Peter; Sagitov, Serik
Abstract : A population has two types of individuals, with each occupying an island. One of those, where individuals of type 1 live, offers a variable environment. Type 2 individuals dwell on the other island, in a constant environment. Only one-way migration (1 → 2 ) is possible. We study then asymptotics of the survival probability in critical and subcritical cases.